A Non-invasive method for assessment of intravascular fluid status: Inferior vena cava diameters and collapsibility index - SANRI, ERKMAN; KARACABEY, SİNAN (PROFESSIONAL MEDICAL PUBLICATIONS, 1969)
Objective: To evaluate the correlation between central venous pressure (CVP) and inferior vena cava (IVC) diameters measured by ultrasonography (Ultrasound) in critically ill patients. Methods: Intubated critically ill patients were enrolled. The CVP values were measured using a U-tube manometer and were compared to the IVC diameters and collapsibility index, which were measured by bedside Ultrasound. Patients younger than 18 years old, who were not intubated, who had an abdominal pressure greater than 12 mmHg, and/or who were admitted for trauma were excluded from the study. Results: Eighty three patients with a mean age of 73.6 +/- 11.2 years were enrolled. The most common diagnosis was sepsis (21 patients, 25.30%). IVC inspiration measurements were statistically significantly correlated with CVP measurements (p0.05, r: 0.1). IVC collapsibility measurements showed a negative correlation with CVP measurements (p<0.01, r: 0.68). Conclusions: There is a strong correlation between CVP and IVC diameters and the collapsibility index. This is a new formula for evaluating CVP, based on our statistical analyses.
Keywords: Ultrasonography; Intubation; End-tidal capnography; SONOGRAPHIC MEASUREMENT; ULTRASONOGRAPHY; CARE; ECHOCARDIOGRAPHY; GUIDELINES; UTILITY; MARKER